2019
DOI: 10.1080/20477724.2019.1632062
|View full text |Cite
|
Sign up to set email alerts
|

Virulence gene profiles of Shigella species isolated from stool specimens in India: its association with clinical manifestation and antimicrobial resistance

Abstract: Shigella is the major cause of bacillary dysentery worldwide, especially in developing countries. There are several virulence factors essential for the organism to be virulent which are generally present in the virulence plasmid and on chromosomal pathogenicity islands. The present study was undertaken to determine the virulence gene profile of Shigella spp isolated from a clinical specimen and to study their significant association with common clinical symptoms and antimicrobial resistance. Sixty Shigella who… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…The S. flexneri isolate harboured secretion autotransporter toxin sat and sepA which is associated with intense abdominal pain [ 64 ]. However, S. sonnei isolates exhibited higher numbers of virulence genes, including senB and sigA associated with bloody diarrhoea and fever respectively [ 65 ]. Presence of isolates with high levels of both AMR and virulence factors could be a consequence of clinically severe cases requiring antibiotics and exerting selective pressure and are a public health concern due to the challenge this poses to outbreak management.…”
Section: Discussionmentioning
confidence: 99%
“…The S. flexneri isolate harboured secretion autotransporter toxin sat and sepA which is associated with intense abdominal pain [ 64 ]. However, S. sonnei isolates exhibited higher numbers of virulence genes, including senB and sigA associated with bloody diarrhoea and fever respectively [ 65 ]. Presence of isolates with high levels of both AMR and virulence factors could be a consequence of clinically severe cases requiring antibiotics and exerting selective pressure and are a public health concern due to the challenge this poses to outbreak management.…”
Section: Discussionmentioning
confidence: 99%
“…Virulence gene presence and frequencies for our S. sonnei cluster were considered normal, since many hallmarks of S. sonnei were detected, such as celb , gad , lpfA , senB , and sigA ( 29 , 30 ). The low detection frequency of some of the virulence genes ( capU and ipaD ) can be attributed to their location on the large virulence plasmid, which can be highly unstable in storage or in laboratory media and is therefore commonly lost upon subculturing ( 31 ).…”
Section: Discussionmentioning
confidence: 99%
“…46,47 The presence of several virulence factors and toxins are associated with the pathogenicity of Shigella spp. 48,49 Bloody diarrhoea, which is a critical condition observed in shigellosis, is induced by the sen gene and has been reported across all species of Shigella. [49][50][51] It has been reported that dehydration in shigellosis leading to watery diarrhoea is potentially caused by the set1B gene predominantly found only in S. flexneri.…”
Section: Discussionmentioning
confidence: 99%
“…48,49 Bloody diarrhoea, which is a critical condition observed in shigellosis, is induced by the sen gene and has been reported across all species of Shigella. [49][50][51] It has been reported that dehydration in shigellosis leading to watery diarrhoea is potentially caused by the set1B gene predominantly found only in S. flexneri. 52,53 Recent studies have shown that S. flexneri possesses more virulent factors compared to other Shigella spp.…”
Section: Discussionmentioning
confidence: 99%